Design and Application of Drive and Protection Circuit of 6 500 V IGBT Based on 1SC0450V - WANG Lei; YANG Lu; LI Shourong; GAO Sheng (机车电传动)
The drive characteristics of 1SC0450V was introduced in detail, and the implementation principle of drive supply circuit, supply under-voltage protection, advanced active clamp and short-circuit protection were analyzed. 6 500 V IGBT drive and protection circuit was given as well, which was based on 1SC0450V. The power units of single 6 500 V IGBT and two parallel 6 500 V IGBT were designed, which were successfully tested on converter test and short-circuit test at last. The experimental waveforms and testing data of the power units was provided. This good protection performance of the drive was verified for applications requiring high reliability in industry and traction.